Bounded Motions of the Dynamical Systems Described by Differential Inclusions - Nihal Ege; Khalik G. Guseinov (Abstract and Applied Analysis)
The boundedness of the motions of the dynamical system described by a differential inclusion with control vector is studied. It is assumed that the right-hand side of the differential inclusion is upper semicontinuous. Using positionally weakly invariant sets, sufficient conditions for boundedness of the motions of a dynamical system are given. These conditions have infinitesimal form and are expressed by the Hamiltonian of the dynamical system.